CURRICULUM AND ISLAMIC TEACHING IN SCHOOL PALACE OF PALEMBANG SULTANET - Abdurrahmansyah Abdurrahmansyah; Nurseri Hasnah Nasution (Conciencia, 2020)
This study aims to analyze the curriculum and Islamic learning model in the Palembang Sultanate Palace. This research is important because it reveals the history of the curriculum and learning traditions among the relatives of the palace which has long been known to be very effective in forming a cadre of productive scholars from among the relatives of the palace. By using a social history approach to Islamic education, this research can reveal several important issues, namely to reaffirm the research explanation that the phenomenon of learning in the palace environment took the form that was commonly practiced in the Islamic education tradition at that time in the form of applying a learning model using lecturing and question and answer strategies. Furthermore, the structure of the education curriculum in the palace environment includes areas of Islamic scholarship such as aqidah, al-Qur'an, interpretation, hadith, dates, fiqh, Arabic, and Sufism. The last field, namely Sufism, is a nuance that characterizes Islamic teaching in the Palembang palace environment. All relatives of the Palembang palace who were taught by the teaching scholars in the "palace school" environment of the Palembang palace were adherents of the Sammaniyah order. From the aspect of implementation of learning in the Palembang palace, the individual and group learning models are quite dominant with an emphasis on the role model and the example of the teaching scholars in the palace environment. The students consisting of relatives of the palace were very familiar with the pattern of education by prioritizing the morals of Sufism. The education model in the palace is very effective in shaping the intellectual tradition and maintaining the continuity of the function and role of the clergy in Palembang, which is dominated by scholars who come from among the relatives of the palace. This pattern of sustainability is then able to preserve the tradition of teaching Islam in the Palembang area and even to various rural areas in the South Sumatra region.